Cardiovascular Disease Risk Factors, Musculoskeletal Health, Physical Fitness, and Occupational Performance in Firefighters: A Narrative Review. (19th September 2022) - Ras, Jaron; Smith, Denise L.; Kengne, Andre P.; Soteriades, Elpidoforos E.; Leach, Lloyd
Abstract : Introduction . Firefighting is a strenuous occupation that requires firefighters to be in peak physical condition. However, many firefighters have risk factors for cardiovascular disease, impaired musculoskeletal health, and are not physically fit for duty, which all negatively impact their occupational performance. Therefore, the aim of this review is to determine the relationship between cardiovascular disease risk factors, musculoskeletal health, physical fitness, and occupational performance in firefighters. Methods . The electronic databases PubMed, SCOPUS, and Web of Science were searched online via the library portal of the University of the Western Cape. Publications and grey literature between the years 2000 to present were used. In total, 2607 articles were identified; after the removal of duplicates 1188 articles were then screened, and were excluded for not meeting initial screening criteria. The remaining 209 full-text articles were screened based on the inclusion and exclusion criteria, where 163 articles were excluded. Only studies that were quantitative were included. This left 46 articles that were then finally included in the current narrative review. Results . The current literature indicated that significant relationships existed between cardiovascular risk factors, musculoskeletal health, physical fitness, and occupational performance. The results indicated firefighters who were aged, obese, physically inactive, cigarette smokers, and unfit were at the highest risk for cardiovascular and musculoskeletal health complications, and unsatisfactory occupational performance. Musculoskeletal health complications significantly affected occupational performance and work ability and were related to physical fitness of firefighters. Most cardiovascular risk factors were related to physical fitness, and all physical fitness parameters were related to occupational performance in firefighters. Conclusion . The overwhelming evidence in the current review established that physical fitness is related to occupational performance. However, the relationship between cardiovascular risk factors and musculoskeletal health in relation to occupational performance is less clear and still understudied. Significant gaps remain in the literature.